Applicatin of Some Evapotranspiration Models at Tropical Region - Slamet Suprayogi; Budi Indra Setiawan; Lilik Budi Prasetyo (PERTETA, 2003)
Potential evaporation (ETp) can be calculated by ETp models climatological parametrs. Among them, the Penman model is most frequently used for ETp estimation. The penman model requires five climatic parameters : temperature, relative humidity, wind, saturation vapor pressure, and net radiation. It also uses complicated unit conversions and lengthy calculation. There are a simple models such as : Jensen - Haise models, Hargreaves, Radiation, Turc's, and Makkink's model. These models that requires only two climatic parameters, temperature and incident radiation.